Knowledge Regarding HIV/AIDS Among the Adult Population in a Rural Community (Journal of Armed Forces Medical College, Bangladesh, 2014)
Introduction: The consequences of HIV/AIDS are alarming. It causes not only loss of live but also social and economic disruption. Being deadly disease, HIV/AIDS has become an important issue of recent times throughout the world. To date, little is known about awareness of HIV/AIDS in Bangladesh. Objectives: To assess the level of knowledge regarding Human Immunodeficiency Virus (HIV)/ Acquired Immune Deficiency Syndrom (AIDS) among the adult population of a rural community. Place and Period of study: the study was done at Tepir Bari, Saitalia, Tengra village under Teli Hati union of Shreepur Upazilla in Gazipur district during the study period of 27 March 2010 to 31 April 2011. Materials and Methods: This cross sectional type of study was conducted with 360 respondents. Semi structured interview schedule was used for collection of information and sampling technique was selective cluster sampling. Results: Among the total 360 respondents 92.5% respondents had knowledge regarding HIV/AIDS and 7.50% had no knowledge about HIV/AIDS. The respondents who were familiar with the term of HIV/AIDS, 86.79% had gathered information from mass media. Most of respondents 83.78% consider that sexual route is the principal means of spreading HIV/AIDS. According to them the other most common ways of spreading HIV/AIDS were sharing same needle (49.55%), through blood and blood products (43.24%), vertical transmission 19.21%. Among 333 respondents,64.72% considered that the top most high risk group was commercial sex workers. 55% considered individuals sharing same needle, 40.2% thought individuals having illegal relationships, 23.33% considered unsafe blood recipients, 11.11% considered drivers, 10.28% considered frequent traveler and 15.83% respondents had no knowledge about high risk groups. Regarding the knowledge about preventing HIV/AIDS majority of respondents (64.44%) considered that the safe sexual behavior is the main way to prevent HIV/AIDS. 32.22% respondents considered using unshared needle, 28.89% respondents thought health education regarding AIDS, 26.44% individuals thought proper maintenance of religious values, 21.44% considered proper screening where as 16.11% respondents had no knowledge about preventive measures. Conclusion: Among the study subjects majority of the respondents had knowledge regarding HIV/AIDS and few had no knowledge and they need information and health education. DOI: http://dx.doi.org/10.3329/jafmc.v9i1.18737 Journal of Armed Forces Medical College Bangladesh Vol.9(1) 2013: 90-97